Strengthening vocational character for polytechnic education which has non-production-based curriculum - Handayani, Peni; Brodjonegoro, Satryo Soemantri (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2015)
The vocational character of polytechnic education has declined in the last ten years, especially for polytechnic which has non-production-based curriculum. This research aims to reveal factors which have contribution in the devocationalization of polytechnic education, and to find out the alternative solution to revocationalize by considering the current condition and the future demand. This study applied qualitative approach supported by quantitative data that involved three polytechnics in Bandung and Malang, three industries in Bandung, one industry in Yogyakarta, and an expert as representative from the Department of Industrial and Cooperation Yogyakarta. Interpretational inductive analysis was used to analyze qualitative data. This study revealed: (1) environmental factors are very influential factor in shaping the character of polytechnic education and recognition; (2) the greatest gaining vocational character acquired through apprenticeship in industry or workplace; and (3) gaining vocational character needs to be managed by maintain and strengthen cooperation between polytechnic and industries, and competent institution which can develop education system.